Impaired implicit learning and feedback processing after stroke. (9th February 2016) - Lam, J.M.; Globas, C.; Hosp, J.A.; Karnath, H.-O.; Wächter, T.; Luft, A.R.
Highlights: Stroke survivors have deficits in feedback-driven implicit learning. Stroke subjects show reduced brain activation in circuits related to feedback-based decision making. Learning-impairment is associated with lesions in frontal areas, putamen, thalamus, caudate and insula. Abstract: The ability to learn is assumed to support successful recovery and rehabilitation therapy after stroke. Hence, learning impairments may reduce the recovery potential. Here, the hypothesis is tested that stroke survivors have deficits in feedback-driven implicit learning. Stroke survivors ( n = 30) and healthy age-matched control subjects ( n = 21) learned a probabilistic classification task with brain activation measured using functional magnetic resonance imaging in a subset of these individuals (17 stroke and 10 controls). Stroke subjects learned slower than controls to classify cues. After being rewarded with a smiley face, they were less likely to give the same response when the cue was repeated. Stroke subjects showed reduced brain activation in putamen, pallidum, thalamus, frontal and prefrontal cortices and cerebellum when compared with controls. Lesion analysis identified those stroke survivors as learning-impaired who had lesions in frontal areas, putamen, thalamus, caudate and insula. Lesion laterality had no effect on learning efficacy or brain activation. These findings suggest that stroke survivors have deficits in reinforcement learning that may be related to dysfunctional processing of feedback-based decision-making, reward signals and working memory.